Physical education in China, as component of the mass physical culture - Van Syue Man (Fizičeskoe Vospitanie Studentov, 2009)
In the article are considered results of the study of the scientific literature and the document, concerning systems of the physical education in China. The results of the study have shown that in China on modern stage forms трехуровневая system of the athletic formation. Each level of this system prepares the alumnus to the following level of the reception practical and theoretical knowledges on physical culture. The study is revealled that Chinas state policy in sphere of the physical education is directed on preparation sound athletic-formed young people capable to high efficiency of the labour and active vital activity.